2013
DOI: 10.1175/jcli-d-12-00417.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Land and Ocean Components of the Global Carbon Cycle in the CMIP5 Earth System Models

Abstract: The authors assess the ability of 18 Earth system models to simulate the land and ocean carbon cycle for the present climate. These models will be used in the next Intergovernmental Panel on Climate Change (IPCC) Fifth Assessment Report (AR5) for climate projections, and such evaluation allows identification of the strengths and weaknesses of individual coupled carbon–climate models as well as identification of systematic biases of the models. Results show that models correctly reproduce the main climatic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
520
2
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 452 publications
(556 citation statements)
references
References 120 publications
32
520
2
2
Order By: Relevance
“…Large inter-model disagreements were found for NPP and heterotrophic respiration (Rh). In agreement with Anav et al (2013), Shao et al (2013) also noted that the CMIP5 historical simulations tend to overestimate photosynthesis and LAI. Todd-Brown et al (2013) compared and evaluated 11 CMIP5 ESMs in terms of their variations in soil carbon.…”
Section: T Ziehn Et Al: Access-esm1 Historical Simulationssupporting
confidence: 77%
See 4 more Smart Citations
“…Large inter-model disagreements were found for NPP and heterotrophic respiration (Rh). In agreement with Anav et al (2013), Shao et al (2013) also noted that the CMIP5 historical simulations tend to overestimate photosynthesis and LAI. Todd-Brown et al (2013) compared and evaluated 11 CMIP5 ESMs in terms of their variations in soil carbon.…”
Section: T Ziehn Et Al: Access-esm1 Historical Simulationssupporting
confidence: 77%
“…In contrast, for the ocean an underestimation of the net primary production (NPP) was noted for a number of models. Anav et al (2013) also found significant regional variations in model performance.…”
Section: T Ziehn Et Al: Access-esm1 Historical Simulationsmentioning
confidence: 84%
See 3 more Smart Citations